Distinct Molecular Epidemiology, Transmission Patterns, and Resistance Mutations of HIV-1 Subtypes A1, A6, and A7 in Bulgaria - Aleksandra Partsuneva; Anna Gancheva; Reneta Dimitrova; Lyubomira Grigorova; Asya Kostadinova; Maria Nikolova; Radoslava Emilova; Nina Yancheva; Rusina Grozdeva; Ivailo Alexiev (Microorganisms)
By 2022, Bulgaria’s National Reference Laboratory had confirmed 4024 HIV cases. We analyzed 132 pol gene sequences to characterize the molecular epidemiology of HIV-1 subtypes A1, A6, and A7 (2001–2022). A1 accounted for 50.0% (66/132) of cases, increasing after 2014, with peaks in 2019 and 2022. A6 comprised 48.5% (64/132), dominating from 2005 to 2014 before stabilizing. A7 was rare (1.5%, 2/132), detected in 2003 and 2011. Transmission patterns varied: A1 was linked to men who have sex with men (MSM) (62.1%), while A6 was primarily heterosexual (HET) (82.8%) with a balanced gender distribution (56.3% male, 43.8% female). Resistance mutations were identified in 29.6% of cases, with A6 showing higher rates of nucleoside reverse transcriptase inhibitor (NRTI) (20.3%) and non-nucleoside reverse transcriptase inhibitor (NNRTI) (7.8%) resistance than A1. Phylogenetic analysis revealed that 13 Bulgarian sequences (9.8%) were involved in transmission clusters, including 10 (7.6%) from sub-subtype A1 and 3 (2.3%) from sub-subtype A6, highlighting distinct genetic diversity and transmission patterns. Despite significant migration from Ukraine in 2022, A6 prevalence remained unchanged, suggesting localized transmission dynamics. These findings highlight a shifting HIV-1 sub-subtype distribution in Bulgaria and emphasize the need for targeted prevention, diagnosis, and treatment strategies tailored to the evolving molecular landscape.